Social Networking Sites (Sns) Quality, Attitude Towards Sns, Type Of Sns And Effective Recruitment Among Human Resource Personnel At Manufacturing Companies In Penang - Abdul Hamid, Muhammad Zafran (2020)
In the manufacturing industry, employers are expected the high achievement in profit. Successfully in business is very important for company to be grow and advance in the future. The achievement is fully depend on the people who are working and give a service towards company. High achievement employees come from the quality of employees. The quality employees are scarcely to be found if the employers still depend on traditional recruitment. In the modern era, the role of social networking sites is not just for social purpose but it also help Human Resource Personnel to select the best pool of candidates. Thus, the present study investigates the relationship between social networking sites quality, attitude toward social networking sites, type of social networking sites and effective recruitment among Human Resource Personnel at Manufacturing Companies in Penang.